Effect of Curing Temperature on Mechanical Properties of Fly Ash-Based Geopolymer Concrete from Bengkayang Power Plant - Syavanka, Lucky Nur; Herwani, Herwani; Faisal, Faisal (Fakultas Teknik Universitas Tanjungpura, 2025)
The production of portland cement generates carbon dioxide emissions, which contribute to environmental degradation. To address this issue, researchers have explored the use of coal waste, such as fly ash, as a partial replacement for cement. This research investigates the potential of fly ash as a substitute in the production of geopolymer concrete. The research follows an experimental approach involving the fabrication of test specimens to evaluate the concrete's mechanical properties. The process encompasses material analysis, specimen preparation, curing, and testing for volume weight, compressive strength, split tensile strength, and elasticity modulus. The findings reveal that the volume weight values range between 2.260,000 kg/m ³ and 2.336,395 kg/m ³, while compressive strength varies from 10,152 MPa to 16,994 MPa. Additionally, the split tensile strength falls within 1,415 MPa to 1,556 MPa, and the elasticity modulus spans from 2.727,352 MPa to 3.325,204 MPa. The results emphasize the significant influence of temperature variations on the mechanical performance of geopolymer concrete, with 60 °C identified as the optimal curing temperature for achieving the highest compressive strength, split tensile strength, and elasticity modulus.